Analisis Quality Control pada Produk Omiland Kasur Bayi Untuk Meminimalisir Produk Cacat di PT. Wahana Kasih Mulia - Anisha Dian Iswahyuni; Aji Kusumastuti Hendrawan; Hasan Nur Syamsi (Pusat riset dan Inovasi Nasional, 2022)
Quality control is one of the obstacles experienced by PT. Wahana Kasih Mulia on CV. KKN. Quality control is an important thing that must be done by companies to minimize defective products. To be able to analyze product defects, researchers use the six sigma model, by formulating the Define, Measure, Analyze, Improve, Control (DMAIC) stages. The purpose of this study was to determine the level of quality control using the DMAIC method with the Six Sigma model applied to manufacturing companies. The results showed that from the measurement of the number of Omiland brand baby mattress products in the January-October 2021 period, it was found that defective products came from three main causes of disability. The distribution data of the number of product quality characteristics and company performance are at the sigma level of 3.50 with a DPMO value of 27,082.275. This shows that the company has not been able to meet process quality standards. Based on this research, the recommendations for improvement given are that the company needs to provide periodic training to employees, perform maintenance on machines, apply a clearer and more detailed Standard Operating Procedure (SOP), conduct tighter supervision of newly arrived raw materials and the company needs to place quality control at every stage of the production process.